{{ 'ml-label-loading-course' | message }}

{{ tocSubheader }}

{{ 'ml-toc-proceed-mlc' | message }}

{{ 'ml-toc-proceed-tbs' | message }}

An error ocurred, try again later!

Chapter {{ article.chapter.number }}

{{ article.number }}. # {{ article.displayTitle }}

{{ article.intro.summary }}

Show less Show more Lesson Settings & Tools

| {{ 'ml-lesson-number-slides' | message : article.intro.bblockCount }} |

| {{ 'ml-lesson-number-exercises' | message : article.intro.exerciseCount }} |

| {{ 'ml-lesson-time-estimation' | message }} |

This lesson will discuss how to apply different transformations to quadratic functions.
### Catch-Up and Review

**Here are a few recommended readings before getting started with this lesson.**

Challenge

The graph of the quadratic function $f(x)=-x_{2}+2x+1$ is drawn on the coordinate plane. By applying transformations to the parabola that corresponds to $f,$ draw the graph of $g(x)=-x_{2}+4x.$

Discussion

A reflection of a function is a transformation that flips a graph over a line called the line of reflection. A reflection in the $x-$axis is achieved by changing the sign of every output value of the function rule. In other words, the sign of the $y-$coordinate of every point on the graph of a function should be changed. Consider the quadratic parent function $y=x_{2}.$

$Functiony=x_{2} Reflection in thex-axisy=-x_{2} $

The reflection of the corresponding parabola can be shown on a coordinate plane.
A reflection in the $y-$axis is instead achieved by changing the sign of every input value. However, since $(-x)_{2}$ is equivalent to $x_{2},$ reflecting $y=x_{2}$ in the $y-$axis does not change the graph. For this reason, the reflection of the graph of another quadratic function will be shown.

$Functiony=(x−1)_{2} Reflection in they-axisy=(-x−1)_{2} $

This transformation can also be shown on a coordinate plane. Example

Kriz is given an extra credit math assignment about quadratic functions and parabolas. The assignment consists of four tasks. For the first task, Kriz is given the graph of the function $y=21 (x+2)_{2}+1.$

Help Kriz with their extra credit assignment.

a Reflect the given parabola in the $x-$axis and write its corresponding equation.

b Reflect the given parabola in the $y-$axis and write its corresponding equation.

a **Graph:**

**Equation:** $y=-21 (x+2)_{2}−1$

b **Graph:**

**Equation:** $y=21 (x−2)_{2}+1$

a Recall that the graph of $y=-f(x)$ is a reflection of the graph of $y=f(x)$ in the $x-$axis.

b The graph of $y=f(-x)$ is a reflection of the graph of $y=f(x)$ in the $y-$axis.

a The reflection of the graph of $y=f(x)$ in the $x-$axis is given by the equation of $y=-f(x).$

$Given Functionf(x)=21 (x+2)_{2}+1Reflection in thex-axis-f(x)=-(21 (x+2)_{2}+1)⇕-f(x)=-21 (x+2)_{2}−1 $

Therefore, the graph of $y=-21 (x+2)_{2}−1$ is a reflection of the graph of $y=21 (x+2)_{2}+1$ in the $x-$axis.
b The reflection of the graph of $y=f(x)$ in the $y-$axis is given by the equation of $y=f(-x).$

$Given Functionf(x)=21 (x+2)_{2}+1Reflection in they-axisf(-x)=21 (-x+2)_{2}+1 $

To obtained equation can be simplified.
$f(-x)=21 (-x+2)_{2}+1$

NegBaseToPosPow

$(-a)_{2}=a_{2}$

$f(-x)=21 (-(-x+2))_{2}+1$

Distr

Distribute $-1$

$f(-x)=21 (x−2)_{2}+1$

Explore

In the coordinate plane, the parabola that corresponds to the quadratic function $y=af(bx)$ can be seen. Observe how the graph is vertically and horizontally stretched and shrunk by changing the values of $a$ and $b.$

Discussion

A function graph is vertically stretched or shrunk by multiplying the output of a function rule by some constant $a,$ where $a>0.$ This constant must be positive, otherwise a reflection is involved. Consider the quadratic function $y=x_{2}+1.$
*stretched* by a factor of $a.$ Conversely, if $a$ is less than $1,$ the graph is vertically *shrunk* by a factor of $a.$ If $a=1,$ then there is no stretch nor shrink. Here, the $y-$coordinates of all points on the graph are multiplied by the factor $a.$
*shrunk* by a factor of $b.$ Conversely, if $b$ is less than $1,$ the graph is horizontally *stretched* by a factor of $b.$ If $b=1,$ then there is neither a stretch nor shrink of the graph. Here, the $x-$coordinates of all points on the graph are multiplied by the factor $b1 .$

$Functiony=x_{2}+1 Vertical Stretch/Shrinkby a Factor ofay=a(x_{2}+1) $

If $a$ is greater than $1,$ the parabola is vertically
Similarly, a function graph is horizontally stretched or shrunk by multiplying the input of a function rule by some constant $b,$ where $b>0.$ Again, the constant must be positive because if it was negative, a reflection would be required.

$Functiony=x_{2}+1 Horizontal Stretch/Shrinkby a Factor ofby=(bx)_{2}+1 $

In this case, if $b$ is greater than $1,$ the graph is horizontally
The information about vertical and horizontal stretches and shrinks of the graph of a function $f$ can be summed up in a table.

Vertical | Horizontal | |
---|---|---|

Stretch | $af(x),$ with $a>1$ | $f(ax),$ with $0<a<1$ |

Shrink | $af(x),$ with $0<a<1$ | $f(ax),$ with $a>1$ |

Example

Kriz's second task is about horizontal and vertical stretches and shrinks of parabolas.

They are given the quadratic function $y=x_{2}−3$ and want to write the function rules of two related functions.

a A quadratic function whose graph is a vertical stretch of the graph of $y=x_{2}−3$ by a factor of $2.$

{"type":"text","form":{"type":"math","options":{"comparison":"1","nofractofloat":false,"keypad":{"simple":false,"useShortLog":false,"variables":["x"],"constants":[]}},"text":"<span class=\"katex\"><span class=\"katex-html\" aria-hidden=\"true\"><\/span><\/span>"},"formTextBefore":"<span class=\"katex\"><span class=\"katex-html\" aria-hidden=\"true\"><span class=\"base\"><span class=\"strut\" style=\"height:0.625em;vertical-align:-0.19444em;\"><\/span><span class=\"mord mathdefault\" style=\"margin-right:0.03588em;\">y<\/span><span class=\"mspace\" style=\"margin-right:0.2777777777777778em;\"><\/span><span class=\"mrel\">=<\/span><\/span><\/span><\/span>","formTextAfter":null,"answer":{"text":["2(x^2-3)","2x^2-6"]}}

b A quadratic function whose graph is a horizontal shrink of the graph of $y=x_{2}−3$ by a factor of $4.$

{"type":"text","form":{"type":"math","options":{"comparison":"1","nofractofloat":false,"keypad":{"simple":false,"useShortLog":false,"variables":["x"],"constants":[]}},"text":"<span class=\"katex\"><span class=\"katex-html\" aria-hidden=\"true\"><\/span><\/span>"},"formTextBefore":"<span class=\"katex\"><span class=\"katex-html\" aria-hidden=\"true\"><span class=\"base\"><span class=\"strut\" style=\"height:0.625em;vertical-align:-0.19444em;\"><\/span><span class=\"mord mathdefault\" style=\"margin-right:0.03588em;\">y<\/span><span class=\"mspace\" style=\"margin-right:0.2777777777777778em;\"><\/span><span class=\"mrel\">=<\/span><\/span><\/span><\/span>","formTextAfter":null,"answer":{"text":["(4x)^2-3","16x^2-3"]}}

a A function graph is vertically stretched or shrunk by multiplying the function rule by a positive constant. If the constant is greater than $1,$ the graph is vertically stretched. Therefore, if the graph of the given function is to be vertically stretched by a factor of $2,$ the function rule must be multiplied by $2.$

$Functiony=x_{2}−3 Vertical Stretchby a Factor of2y=2(x_{2}−3) $

Recall that stretching a graph by a factor of $2$ means multiplying the $y-$coordinates of all the points on the curve by a factor of $2.$ This can be seen in a coordinate plane.
It is worth noting that the resulting function can be simplified by distributing $2.$

$y=2(x_{2}−3)⇔y=2x_{2}−6 $

b A function graph is horizontally stretched or shrunk by multiplying the input of the function rule by a positive constant. If the constant is greater than $1,$ the graph is horizontally shrunk. Therefore, to horizontally shrink the graph by a factor of $4,$ the input of the function rule must be multiplied by $4.$

$Functiony=x_{2}−3 Horizontal Shrinkby a Factor of4y=(4x)_{2}−3 $

This can be seen in a coordinate plane.
It is worth noting that the resulting function can be simplified by using the Power of a Product Property.

$y=(4x)_{2}−3⇔y=16x_{2}−3 $

Pop Quiz

The graph of the quadratic function $y=x_{2}$ is shown in the coordinate plane. The graph of a horizontal or vertical stretch or shrink is also shown.

Example

Kriz's assignment is getting more interesting, as the third task is about combining reflections with vertical and horizontal stretches and shrinks.

This time, they are given the quadratic function $y=(x−1)_{2}$ and want to write the function rules of two other functions.

a A quadratic function whose graph is a vertical stretch by a factor of $3$ followed by a reflection in the $y-$axis of the graph of $y=(x−1)_{2}.$

{"type":"text","form":{"type":"math","options":{"comparison":"1","nofractofloat":false,"keypad":{"simple":false,"useShortLog":false,"variables":["x"],"constants":[]}},"text":"<span class=\"katex\"><span class=\"katex-html\" aria-hidden=\"true\"><\/span><\/span>"},"formTextBefore":"<span class=\"katex\"><span class=\"katex-html\" aria-hidden=\"true\"><span class=\"base\"><span class=\"strut\" style=\"height:0.625em;vertical-align:-0.19444em;\"><\/span><span class=\"mord mathdefault\" style=\"margin-right:0.03588em;\">y<\/span><span class=\"mspace\" style=\"margin-right:0.2777777777777778em;\"><\/span><span class=\"mrel\">=<\/span><\/span><\/span><\/span>","formTextAfter":null,"answer":{"text":["3(-x-1)^2","3(x+1)^2","3(x^2+2x+1)","3x^2+6x+3"]}}

b A quadratic function whose graph is a horizontal shrink by a factor of $2$ followed by a reflection in the $x-$axis of the graph of $y=(x−1)_{2}.$

{"type":"text","form":{"type":"math","options":{"comparison":"1","nofractofloat":false,"keypad":{"simple":false,"useShortLog":false,"variables":["x"],"constants":[]}},"text":"<span class=\"katex\"><span class=\"katex-html\" aria-hidden=\"true\"><\/span><\/span>"},"formTextBefore":"<span class=\"katex\"><span class=\"katex-html\" aria-hidden=\"true\"><span class=\"base\"><span class=\"strut\" style=\"height:0.625em;vertical-align:-0.19444em;\"><\/span><span class=\"mord mathdefault\" style=\"margin-right:0.03588em;\">y<\/span><span class=\"mspace\" style=\"margin-right:0.2777777777777778em;\"><\/span><span class=\"mrel\">=<\/span><\/span><\/span><\/span>","formTextAfter":null,"answer":{"text":["-(2x-1)^2","-1(2x-1)^2","-(4x^2-4x+1)","-1(4x^2-4x+1)","-4x^2+4x-1"]}}

a A function graph is vertically stretched or shrunk by multiplying the function rule by a positive constant. If the constant is greater than $1,$ the graph is vertically stretched. Therefore, if the graph of the given function is to be vertically stretched by a factor of $3,$ the *function rule* must be multiplied by $3.$

$Functiony=(x−1)_{2} Vertical Stretchby a Factor of3y=3(x−1)_{2} $

Furthermore, a function graph is reflected in the $y-$axis by changing the $sign$ of the input.
$Functiony=3(x−1)_{2} Reflection in they-axisy=3(-x−1)_{2} $

These transformations are illustrated by the following diagram.
The resulting function can be simplified by squaring the binomial and then distributing the $3.$

$y=3(-x−1)_{2}$

▼

Simplify right-hand side

NegBaseToPosPow

$(-a)_{2}=a_{2}$

$y=3(-(-x−1))_{2}$

Distr

Distribute $-1$

$y=3(x+1)_{2}$

ExpandPosPerfectSquare

$(a+b)_{2}=a_{2}+2ab+b_{2}$

$y=3(x_{2}+2x(1)+1_{2})$

BaseOne

$1_{a}=1$

$y=3(x_{2}+2x(1)+1)$

IdPropMult

Identity Property of Multiplication

$y=3(x_{2}+2x+1)$

Distr

Distribute $3$

$y=3x_{2}+6x+3$

b A function graph is horizontally stretched or shrunk by multiplying the input of the function rule by a positive constant. If the constant is greater than $1,$ the graph is horizontally shrunk. Therefore, to horizontally shrink the graph by a factor of $2,$ the *input* of the function rule must be multiplied by $2.$

$Functiony=(x−1)_{2} Horizontal Shrinkby a Factor of2y=(2x−1)_{2} $

Furthermore, a function graph is reflected in the $x-$axis by changing the $sign$ of the output.
$Functiony=(2x−1)_{2} Reflection in thex-axisy=-(2x−1)_{2} $

The described transformations are demonstrated by the following diagram.
The resulting function can be simplified by squaring the binomial and then distributing the $-1.$

$y=-(2x−1)_{2}$

▼

Simplify right-hand side

ExpandNegPerfectSquare

$(a−b)_{2}=a_{2}−2ab+b_{2}$

$y=-((2x)_{2}−2(2x)(1)+1_{2})$

PowProdII

$(ab)_{m}=a_{m}b_{m}$

$y=-(4x_{2}−2(2x)(1)+1_{2})$

BaseOne

$1_{a}=1$

$y=-(4x_{2}−2(2x)(1)+1)$

Multiply

Multiply

$y=-(4x_{2}−4x+1)$

Distr

Distribute $-1$

$y=-4x_{2}+4x−1$

Explore

In the coordinate plane, the graph of the quadratic function $y=(x−h)_{2}+k$ can be seen. Observe how the graph is horizontally and vertically translated by changing the values of $h$ and $k.$

Discussion

A translation of a function is a transformation that shifts a graph vertically or horizontally. A vertical translation is achieved by adding some number to every output value of a function rule. Consider the quadratic function $y=x_{2}.$
*positive*, then a number is *subtracted* from $x.$ On the other hand, if $h$ is *negative*, a number is *added* to the variable $x.$

$Functiony=x_{2} Vertical TranslationbykUnitsy=x_{2}+k $

If $k$ is a positive number, the translation is performed upwards. Conversely, if $k$ is negative, the translation is performed downwards. If $k=0,$ then there is no translation. This transformation can be shown on a coordinate plane.
A horizontal translation is instead achieved by subtracting a number from every input value.

$Functiony=x_{2} Horizontal TranslationbyhUnitsy=(x−h)_{2} $

In this case, if $h$ is a positive number, the translation is performed to the right. Conversely, if $h$ is negative, the translation is performed to the left. If $h=0,$ then there is no translation. It is worth noting that since $h$ is subtracted from $x,$ if $h$ is
The vertical and horizontal translations of the graph of a function $f$ can be summarized in a table.

Translation | |
---|---|

Vertical | Horizontal |

Upwards$f(x)+k,$ with $k>0$ |
To the Right$f(x−h),$ with $h>0$ |

Downwards$f(x)+k,$ with $k<0$ |
To the Left$f(x−h),$ with $h<0$ |

Example

To finally finish the assignment and get the extra credit they need, Kriz has to finish the fourth task of the math assignment. This time, the graph of the quadratic parent function $y=x_{2}$ is given.

By translating this quadratic function, Kriz wants to draw the graphs and write the equations of the following functions.

a A translation of the graph of $y=x_{2}$ three units up.

b A translation of the graph of $y=x_{2}$ two units to the right.

c A translation of the graph of $y=x_{2}$ one unit down and three units to the left.

a **Equation:** $y=x_{2}+3$

**Graph:**

b **Equation:** $y=(x−2)_{2}$

**Graph:**

c **Equation:** $y=(x+3)_{2}−1$

**Graph:**

b The graph of $y=f(x−h)$ is a horizontal translation of the graph of $y=f(x)$ by $h$ units. If $h$ is positive, the translation is to the right. If $h$ is negative, the translation is to the left.

c The graph of $y=f(x−h)+k$ is a horizontal translation followed by a vertical translation by $h$ and $k$ units, respectively.

a The graph of $y=f(x)+k$ is a vertical translation of the graph of $y=f(x)$ by $k$ units. If $k$ is positive, the translation is upwards. Conversely, if $k$ is negative, then the translation is downwards.

$Functiony=x_{2} Translation3Units Upy=x_{2}+3 $

This can be seen on the coordinate plane.
b The graph of $y=f(x−h)$ is a horizontal translation of the graph of $y=f(x)$ by $h$ units. If $h$ is positive, the translation is to the right. Conversely, if $h$ is negative, then the translation is to the left. Note that since $h$ is subtracted from $x,$ if $h$ is positive, then the number is *subtracted* from $x.$ On the other hand, if $h$ is negative, the number is added to $x.$

$Functiony=x_{2} Translation2Units to the Righty=(x−2)_{2} $

Here, since the given graph is to be translated $2$ units to the right, the value of $h$ is $2.$ Therefore, $2$ is
It is worth noting that the obtained function can be simplified by squaring the binomial.

$y=(x−2)_{2}$

▼

Simplify right-hand side

ExpandNegPerfectSquare

$(a−b)_{2}=a_{2}−2ab+b_{2}$

$y=x_{2}−2x(2)+2$